Bivalvia – a look at the Branches - Bieler, R.; Mikkelsen, P. M. (Zoological Journal of the Linnean Society, 2006)
Systematic research on bivalved molluscs (Mollusca: Bivalvia = Pelecypoda) is briefly reviewed in an introduction to a series of papers focusing on seven of the larger branches of the bivalve tree. These are presented in an attempt to summarize current knowledge, to stimulate new research and to highlight needs for future research focus. A revised classification of extant bivalve families (with synonyms and included subfamilies) is presented, based on information compiled from the latest palaeontological, morphological and molecular data.